2006
DOI: 10.1152/ajplung.00292.2005
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-induced caveolin-1 knockdown in mice increases lung vascular permeability via the junctional pathway

Abstract: Caveolin-1, the principal integral membrane protein of caveolae, has been implicated in regulating the structural integrity of caveolae, vesicular trafficking, and signal transduction. Although the functions of caveolin-1 are beginning to be explored in caveolin-1-/- mice, these results are confounded by unknown compensatory mechanisms and the development of pulmonary hypertension, cardiomyopathy, and lung fibrosis. To address the role of caveolin-1 in regulating lung vascular permeability, in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 51 publications
8
103
1
Order By: Relevance
“…In other experiments in which RNA interference was used to knock down caveolin-1 expression in mouse lung microvessel endothelia, it was shown that 80 -90% decrease in caveolin-1 expression reduced the number of caveolae in ECs and increased albumin transport via the paracellular pathway (107). The opening of the interendothelial junctions and the increased paracellular permeability to albumin were dependent on NO production.…”
Section: Endothelial Caveolae: Specialized Vesicular Carriers With DImentioning
confidence: 95%
“…In other experiments in which RNA interference was used to knock down caveolin-1 expression in mouse lung microvessel endothelia, it was shown that 80 -90% decrease in caveolin-1 expression reduced the number of caveolae in ECs and increased albumin transport via the paracellular pathway (107). The opening of the interendothelial junctions and the increased paracellular permeability to albumin were dependent on NO production.…”
Section: Endothelial Caveolae: Specialized Vesicular Carriers With DImentioning
confidence: 95%
“…There is evidence that caveolae have an important role in transcytosis across endothelial cells (Minshall et al, 2003;Oh et al, 2007), and this is a case in which budding from the membrane is obviously crucial. Intriguingly, transport of various markers from blood vessels to the surrounding tissues is not blocked in caveolin-1-knockout mice (Miyawaki-Shimizu et al, 2006;Schubert et al, 2002). This could be due to increased permeability of the tight junctions between endothelial cells, but compensatory vesicle trafficking and transcytosis cannot be ruled out.…”
Section: Broader Functions For Caveolins and Flotillins?mentioning
confidence: 99%
“…Both caveolinand eNOS-deficient mice show increased vascular permeability at inter-endothelial junctions, suggesting that these molecules are critical for vascular barrier functions in the lungs [9][10][11]. The localisation of eNOS at cellular membranes and its interaction with sphingolipids is considered a key aspect of eNOS signalling and function [12].…”
mentioning
confidence: 99%